1993
DOI: 10.1007/bf00216140
|View full text |Cite
|
Sign up to set email alerts
|

Presence of telomeric and subtelomeric sequences at the fusion points of ring chromosomes indicates that the ring syndrome is caused by ring instability

Abstract: In situ hybridization of a telomeric (TTA-GGG)n sequence to metaphases from three cases of ring chromosome, involving respectively chromosomes 4, 16, and 20, showed the presence of the cognate sequences in all three rings. To investigate whether these ring chromosomes originated by telomere-telomere fusion, we determined, by in situ hybridization, whether telomere-associated sequences and/or specific distal sequences were still present in the ring chromosomes. The finding that these sequences were preserved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 11 publications
4
57
0
Order By: Relevance
“…First, failure of telo mere capping even when some telomeric repeats still remain at a chromosome end suggests that the same could occur in mammalian cells. This might explain why growth arrest of senescent somatic cells in vitro occurs with appreciable telomeric repeat hybridization signal still present at chromosome ends (Counter et al 1992) and why telomere-telomere fusions (telomere as sociations) often occur with telomeric repeats still being detectable at the fusion points (Pezzolo et al 1993;Saltman et al 1993). Second, we have shown that recombi nation is a relatively efficient means of maintaining telomeric repeat arrays in the absence of telomerase.…”
Section: Discussionmentioning
confidence: 99%
“…First, failure of telo mere capping even when some telomeric repeats still remain at a chromosome end suggests that the same could occur in mammalian cells. This might explain why growth arrest of senescent somatic cells in vitro occurs with appreciable telomeric repeat hybridization signal still present at chromosome ends (Counter et al 1992) and why telomere-telomere fusions (telomere as sociations) often occur with telomeric repeats still being detectable at the fusion points (Pezzolo et al 1993;Saltman et al 1993). Second, we have shown that recombi nation is a relatively efficient means of maintaining telomeric repeat arrays in the absence of telomerase.…”
Section: Discussionmentioning
confidence: 99%
“…Kosztolanyi (8) noted that 99% of ring chromosomes are sporadic in origin. Pezzolo et al (9) showed the presence of telomeric and subtelomeric sequences at the fusion points of the ring chromosomes by fluorescence in situ hybridization. This suggested that ring formation may be caused by ring instability and is not necessarily due to the intrinsic loss of genetic information.…”
Section: Commentmentioning
confidence: 99%
“…The Yq subtelomeric DNA sequence has been conserved in the higher primates (PTR, Yq11-qter; GGO, Yq12-qter; and PPY, Yq11-qter) (Fig. 1) although such sequences are known to be highly polymorphic and unstable in the human (Brown et al 1990;Pezzolo et al 1993). The amelogenin gene (AMELY) has also been conserved at the equivalent Molecular phylogenetics of the hominoid Y chromosome Fig.…”
Section: Resultsmentioning
confidence: 99%